Hydration Myths - Lauren Caruso; Karla P. Shelnutt; Gail Kauwell (EDIS)
Whether at school, work, or running errands, it is common to see people sipping on their water bottles. This fashionable trend is a healthy one because water is essential for life. But while most people know that drinking water is good for them, many misconceptions exist about water and hydration. Learn the truth behind some of the most common hydration myths. This 4-page fact sheet was written by Lauren Caruso, Karla P. Shelnutt, and Gail Kauwell, and published by the UF Department of Family, Youth and Community Sciences, August 2014.